Did the adoption of international accounting standards produce a major recognition of intangible assets in Brazil? - Carlos Filho, Francisco de Assis (2013)
This study aims at analyzing whether the transition from local accounting standards to international accounting standarss proposed by the Internationa Accounting Standards Board - IASB resulted in a greater recognition of intangible assets in Brazilian companies and whether there is any correlation between the stock prices of these companies and the information of their intangible assets published in the financial statements. The sample consisted of 213 companies listed on the BM & FBOVESPA in a period of 6 years, from 2005 to 2007 (prior to the adoption of IAS / IFRS), and from 2009 to 2011 (after the adoption of IAS / IFRS). To verify the increase or the decrease of their intangible assets recognition which were identified and the non-identifyed intangible assets (goodwill), a descriptive data analysis was employed, and subsequently two tests were held to compare averages: t-Student and Wilcoxon. The analysis of the correlation between stock price and intangible information was performed by applying a multivaried regression model. The results obtained by using the t-Student test indicated that there was greater recognition by companies with regard to the variables of identifiable intangible assets and total intangible assets. On the other hand, with respect to the variable goodwill, no greater recognition was observed. Finally, with respect to the value of the stock prices and published intangibles, it was found that there is a relationship between the stock prices and recognized total intangible assets.